2018
DOI: 10.1186/s13045-018-0625-1
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes released by hepatocarcinoma cells endow adipocytes with tumor-promoting properties

Abstract: BackgroundThe initiation and progression of hepatocellular carcinoma (HCC) are largely dependent on its local microenvironment. Adipocytes are an important component of hepatic microenvironment in nonalcoholic fatty liver disease (NAFLD), which is a significant risk factor for HCC. Given the global prevalence of NAFLD, a better understanding of the interplay between HCC cells and adipocytes is urgently needed. Exosomes, released by malignant cells, represent a novel way of cell-cell interaction and have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 46 publications
2
110
0
Order By: Relevance
“…Hep3B, SMMC7721, Huh7 and L02 cell line was purchased from American Type Culture Collection (ATCC). All cell lines were cultured in Dulbecco's modification of Eagle's medium (DMEM; Gibco) supplemented with 10% fetal bovine sera (FBS; Gibco) and 1% penicillin‐streptomycin, and maintained in a humidified atmosphere containing 5% CO 2 at 37°C according to the previous studies 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…Hep3B, SMMC7721, Huh7 and L02 cell line was purchased from American Type Culture Collection (ATCC). All cell lines were cultured in Dulbecco's modification of Eagle's medium (DMEM; Gibco) supplemented with 10% fetal bovine sera (FBS; Gibco) and 1% penicillin‐streptomycin, and maintained in a humidified atmosphere containing 5% CO 2 at 37°C according to the previous studies 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…Exosomes released by malignant cells play an important role in cancer cell communication with their microenvironment. HCC cell HepG2-derived exosomes could be actively internalized by adipocytes and caused significant transcriptomic alterations and in particular induced an inflammatory phenotype in adipocytes [14]. Exosomal miRNAs can affect many aspects of physiological and pathological conditions in HCC and indicates that miRNAs in exosomes can not only serve as sensitive biomarkers for cancer diagnostics and recurrence but can also potentially be used as therapeutics to target HCC progression [15].…”
Section: Exosomesmentioning
confidence: 99%
“…Increasing data indicate that macrophages may create an optimal microenvironment for reducing inflammation through a paracrine mechanism [16][17][18], and exosomes secreted by macrophages play an important role in communicating with neighboring cells via regulating levels of cytokines and miRNAs to ameliorate the inflammatory response in recipient cells [19,20]. It has been reported that macrophage-derived exosomes attenuated thermal hyperalgesia in a murine model of inflammatory pain, suggesting their role in dysregulated inflammation [21].…”
Section: Introductionmentioning
confidence: 99%